Answer: The required solution is x = 13.5.
Step-by-step explanation: We are given to solve the following equation :
![(5x+6)/(3x-9)=(7)/(3)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/p6lptf2pdev53r9lp1sgczjdr611p754yq.png)
To solve the given equation (i), we need to cross-multiply first and then solve for x.
The solution of equation (i) is as follows :
![(5x+6)/(3x-9)=(7)/(3)\\\\\Rightarrow 3(5x+6)=7(3x-9)\\\\\Rightarrow 15x+18=21x-63\\\\\Rightarrow 21x-15x=63+18\\\\\Rightarrow 6x=81\\\\\Rightarrow x=(81)/(6)\\\\\Rightarrow x=13.5.](https://img.qammunity.org/2019/formulas/mathematics/middle-school/91uvzhi168pwthca5ycaqaicofdq2gbibb.png)
Thus, the required solution is x = 13.5.